STRATEGI PENGGUNAAN FLYER DI MEDIA SOSIAL SEBAGAI SARANA UNTUK MENARIK MINAT BACA MASYARAKAT - Alfiatu Solikah; Widyasmoro, Hari; Jamroji, Bagus; Khodijah, Siti (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2021)
The purpose of this study is to describe the activities conducted by religious counselors and to assess the public's interest in flyer media for guidance or counseling. Religious counselors have the task of conducting counseling guidance, developing guidance, and professional development. Before conducting counseling guidance, religious counselors must prepare monographs and activity plans, as well as develop guidance materials and evaluation instruments. This research method uses a qualitative approach, with data collection techniques through observation, interviews, and documentary studies. The method used is descriptive. This study concludes: First, the tasks of religious counselors in conducting counseling guidance for the community begin with guidance preparation, counseling/information services, work plan preparation, guidance or counseling material preparation, guidance implementation, counseling assistance, religious problem mediation, guidance monitoring and evaluation, cross-sectoral cooperation activities, guidance or counseling model development, and guidance or counseling guideline preparation; Second, Flyer media can attract the public's/ congregants' interest in reading. In this case, flyer media is distributed through social media, known as e-flyers. Flyers distributed through social networks are faster, more massive, and more focused on the recipients, accompanied by a call to action to encourage readers to continue reading on the religious counselor's blog.